The feminist case against pornography: a review and re-evaluation - Cawston A. (Inquiry (United Kingdom), 2019)
Despite sustained feminist criticism, the production and consumption of pornography does not show signs of waning. Here, I offer a critical review of the existing feminist anti-pornography debate, arguing that it has largely failed to provide suitable grounds for a stable and comprehensive critique, instead often indirectly providing theoretical resources for pornography to reinvent itself. This is a product, in my view, of a misguided focus on the pornographic object. Feminist critics are better served, I argue, by redirecting their critical gaze towards the consumers of pornography, and, in particular, to the attitudes such consumption reflects. To that end, I introduce an alternative, attitudinal approach that enables criticism of pornography as a reflection of sexist attitudes, as well as for its role in concealing these attitudes.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; philosophie; philosophie politique; pornographie; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; santé; sciences humaines; sex1911; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; éthique

Dictionnaire critique du féminisme - Hirata, Helena (Presses universitaires de France, 2004)
Avortement et contraception, citoyenneté, division sexuelle du travail et rapports sociaux de sexe, domination, famille, féminité-masculinité-virilité, harcèlement sexuel, histoire (sexuation de l'), maternité, migration, mixité, mondialisation, mouvements féministes, parité , patriarcat (théories du), précarisation sociale, prostitution, sexualité, transmissions intergénérationnelles, syndicats, travail domestique, violences.dictionnaire est de changer la façon commune de penser " : l'ambition de Diderot est reprise avec force par les auteurs de ce parcours historique etcritique duféminisme . Cette volonté éditoriale s'exprime dans le choix typologique des entrées : des concepts nouveaux issus de la théorisation féministe, des champs d'intervention des luttes féministes, des notions transversales d'économie et de sociologie du travail.Dictionnaire théorique et politique, pluriel et engagé, cet ouvrage se veut aussi un texte de conviction et d'explication.
Keywords: 1900-1999; approches et analyses; avortement; corps; cours; cycles supérieurs; dictionnaire critique; discipline; europe; fem1000; fem7000; france; har4600; histoire et politique; interdisciplinarité; justice reproductive; lit2815; lit3220; lit3495; militance; outils; ouvrages de références; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexualité; sociologie; thématiques; travail